PERAN JOB SATISFACTION DALAM MEMEDIASI HUBUNGAN ANTARA TAMBAHAN PENGHASILAN PEGAWAI DAN WORK ABILITY TERHADAP KINERJA PEGAWAI PADA DINAS KOPERASI DAN USAHA MIKRO KOTA PASURUAN - Farid Hamdany; Muryati Muryati; Survival Survival (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This study aims to obtain empirical evidence of the ability of additional employee income and work ability in encouraging employee performance improvement, either directly or through job satisfaction mediation.This type of research is quantitative with the SEM-SmartPLS method. Data were obtained through questionnaires which were distributed to 34 employees of the Pasuruan City Cooperatives and Micro Business Office.Empirical evidence shows that both additional employee income and work ability are not able to strongly encourage an increase in employee performance, but to job satisfaction both are strong. The role of job satisfaction as a mediation is very strong, both in mediating the effect of additional employee income on employee performance and on the effect of work ability on employee performance. This finding is supported by the descriptive of the four variables, all of which received high responses, including being able to meet the needs of life, being able to solve problems, assessing promotions, and having a commitment to the responsibilities given